Comprehensive characterization of the liquid fraction of digestates from full-scale anaerobic co-digestion. (January 2017) - Akhiar, Afifi; Battimelli, Audrey; Torrijos, Michel; Carrere, Helene
Highlights: High COD content of liquid fractions of digestates from co-digestion. Size distribution is linked to separation process and manure content in the feed. High total nitrogen and high ion concentrations (mainly K +, NH4 + ). Liquid digestate contains mostly suspended solids and colloids. Most organic matter is recalcitrant, thus poor carbon removal in activated sludge. Abstract: Waste management by anaerobic digestion generates a final byproduct, the digestate, which is usually separated into solid and liquid fractions to reduce the volume for transportation. The composition of the solid fraction has been recently studied to allow its valorization. However, full composition of liquid fraction of digestate and its size fractionation are less considered in the literature for efficient post treatment and valorization purposes. Therefore, here we characterized in detail liquid fraction of digestate obtained after solid-liquid separation from 11 full-scale co-digestion plants. The liquid fraction has a high concentration in organic matter with Chemical Oxygen Demand (COD) from 9.2 to 78 g/L with 60–96% of COD in suspended particles (>1.2 μm), 2–27% in colloids (1.2 μm to 1 kDa) and 2–18% in dissolved matter (<1 kDa). Besides, it contained from 1.5 to 6.5 g/L total nitrogen and high ions concentrations (0.5–3.1 g/L NH4 +, 1.05–5.48 g/L K +, 0–2.13 g/L PO4 3− ). In addition, liquid fraction of digestate has poor biodegradability due to presence of humic substances making aerobic treatment inefficient. Only physico-chemical post treatment can be proposed for organic matter removal.